Tilted fiber Bragg grating fixed in a polypropylene tube for ultrasonic sensing and imaging of simulated geological models - Gang, Tingting; Zhang, Xuan; Sun, Ruijuan (Optics and laser technology, 2021)
•A fiber ultrasonic sensor based on TFBG is proposed and demonstrated.•TFBG is packaged in a tilted tube resulting great stability and direction dependence.•2D images of models are reconstructed using time lapse changes in reflected signal. A fiber ultrasonic sensor based on tilted fiber Bragg grating (TFBG) is proposed and demonstrated both in theory and experiment. The sensor probe is packaged in a sturdily tilted polypropylene tube resulting improvements in great stability and direction dependence. In experiments, the proposed sensor performs a high ultrasonic wave (UW) sensitivity and thus it can obtain layers information in rock models. After scanning slope and surface seismic physical models, cross-section imaging of models is achieved finally by data processing and reconstruction.